Association Between Hearing Characteristics/Prognosis and Vestibular Function in Sudden Sensorineural Hearing Loss With Vertigo - Wang, Yixu; Wang, Le; Jing, Yuanyuan; Yu, Lisheng; Ye, Fanglei (Frontiers in Neurology, 2020)
Sudden sensorineural hearing loss (SSNHL) patients with vertigo have a poorer prognosis. However, the factors associated with hearing recovery remain uncertain. This retrospective study was to evaluate the association between hearing characteristics/hearing recovery and the patterns of vestibulocochlear lesions in SSNHL patients with vertigo. Patients were classified into groups according to the patterns of vestibular dysfunction. We not only compared hearing characteristics and prognosis among subgroups but also determined the potential association between vestibular lesion location and hearing recovery. The shapes of the audiogram differed significantly between patients with normal vestibular function and patients with vestibular dysfunction (p=0.022). Patients whose audiogram indicated profound hearing loss were 3.89 times more likely to have vestibular dysfunction than those whose audiogram shape indicated low-frequency hearing loss (95% CI, 1.02 to 14.86, p=0.047). Patients who had saccule dysfunction were 0.11 times as likely to have hearing recovery than those who had normal saccule function (95% CI, 0.11 to 0.31, p=0.001). When adjusted for sex and age, patients who had saccule dysfunction were 0.07 times as likely to have hearing recovery than those who had normal saccule function (95% CI, 0.02 to 0.22, p=0.001). Abnormal results following cVEMP testing may be a potential predictive factor for poor hearing recovery.